ANALYSIS OF THE CRIMINAL ACTION OF EMBRACTION AGAINST CAR RENTAL (A Research in the Legal Area of the Medan District Court) - Novi Juli Rosani Zulkarnain (International Journal of Educational Research Excellence (IJERE), 2022)
Formula problem on study This is application follow criminal fraud sale car for sale return to others, factor happening follow criminal car rental scam so that resulted car for sale to others too effort what is given so that follow criminal resulting car rental scams car for sale No spread wide to society . As for who became objective from study ie For knowing the application of the criminal act of fraudulent selling of cars to other people, knowing the factors of the occurrence of criminal acts of car rental fraud resulting in cars being sold to other people and knowing the efforts made so that the crime of car rental fraud which resulted in cars being sold did not spread widely to the public. Results study This show Application follow criminal fraud embezzlement rental car arranged based on chapter 372, 373, 374 and 375 of the Criminal Code. Based on a number of cases that have outlined on part before , offender embezzlement car snared with demands 4-6 years confinement prison. Factor reason happening follow criminal embezzlement car among them is factor economics, factor ignorance consequence law, factor exists opportunity / chance And factor weak system security rental party. Efforts that can done in countermeasures follow criminal embezzlement rental car ie through action preventive And repressive . Action preventive covers search background behind or reason tenant rental car, request guarantee form of personal data in a manner complete, check vehicle before lease, use driver Alone as well as make letter clear agreement. Action repressive covers enhancement effectiveness police in reveal doer, do investigation And investigation in accordance with the Criminal Procedure Code criminal , tracking And collection accurate evidence.